Fuzzy Dominating Set - V. T. Chandrasekaran; R. Sangeetha (International Journal of Mathematics And its Applications, 2018)
In this paper, we define effective vertex, vertex effective fuzzy graph, fuzzy dominating set of a fuzzy graph. Some properties of minimum fuzzy dominating set are discussed. Bounds of fuzzy dominating number is also studied.